Bi-axial failure response of cross ply GFRP composites : a numerical study - Yash Guleria (2018)
High specific strength, stiffness and damage tolerance dominate the choice of material selection in aviation as well as wind energy sector. Composite materials offer superior weight specific properties and have been extensively used in the aforementioned fields. Due to their anisotropic nature, bi-axial failure response of composites has received significant attention over the years. Apparently, majority of the research has been focused on quasi-isotropic laminate configurations under bi-axial tension, with limited studies on cross ply configurations of glass fibre reinforced polymers (GFRP). With efforts to address this shortfall, the primary aim of the current study was to perform finite element analysis and numerically analyse the failure response of [0/90]s cross ply GFRP laminates, subject to bi-axial tension, tension-compression and combined tension-shear loads. Cruciform and butterfly specimens were modelled using an explicit solver in commercial finite element software ABAQUS®, with Hashin damage as the initiation criteria. Loads were applied under displacement control. Failure mechanisms, load-displacement responses and failure envelops were obtained for the specimen models. For cruciform cross ply laminate, an un-notched specimen was first modelled to study its behaviour and provide a benchmark for the proceeding analysis. It was determined that the cross ply laminates exhibit bi-axial strengthening behaviour for the different notch lengths and orientation angles that were analysed. A shift from notch sensitive to a notch –insensitive behaviour was also observed as the transverse directional load began to dominate, for the 0º notch orientation. 30º and 45º notched specimens showed notch sensitive behaviour for all the load ratios. Although, close co-relation was seen between the numerical analysis and the experiments conducted by previous researchers, deviation of results at certain load ratios which have been documented, still require precise explanation. Butterfly specimen model loaded under tension-shear also showed a notch sensitive response, with a significant reduction in failure strength as the shear load began to dominate, due to the absence of major shear load bearing plies. Intra-laminar crack opening mode, a mixed failure mode and in plane shear failure mode were also identified for the studied load angles.